ANALYSIS OF MILLENIAL GENERATION BEHAVIOR IN FINANCIAL PERSPECTIVE - Dewi Ayu Wulandari (Faculty of Economic and Business, University of Pasundan, 2022)
Nowadays, millennials are at productive age. They are forced to make financial decisions. These decisions require the ability, knowledge, and good financial behavior. This study aims to find out the level of financial capability which is measured by knowledge, skills, and attitude; financial behavior which is measured by practice regarding cash, credit, and saving management, and their effect on financial satisfaction which is measured by subjective assessments of satisfaction of asset, credit, and saving management on millennials in Surabaya, Sidoarjo, Gresik, and Bangkalan regions. Data are obtained through direct and online surveys of 200 millennials using purposive and snowball sampling techniques. The results of this study show that financial capability has a positive effect on financial behavior. The better their financial management ability, the better their financial behavior. Financial behavior has an effect on financial satisfaction and mediates the relation between financial capability and financial satisfaction.